2021
DOI: 10.1002/cche.10498
|View full text |Cite
|
Sign up to set email alerts
|

Development of gluten‐free bread using low‐pressure homogenized rice flour supplemented with faba bean flour

Abstract: Background and objectives: Low-pressure homogenization (30 MPa-3 passes) applied to long (LRF) and medium (MRF) rice grain flours was tested as physical method for improving gluten-free breads (GFB) without additives. Rice flours were blended with faba bean flour (FBF) in the ratio 2:1 (w:w).Findings: Low-pressure homogenization increased damaged starch content of rice flours and decreased the particle size distribution of blends, leading to higher volumes during batters' fermentation. Homogenization treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…As part of physical treatments, low-pressure homogenization has recently been applied with interesting results in GF breadmaking. Boulemkahel et al (2022) reported that long/medium grain rice flours showed reduced particle size and an increased content of damaged starch after being homogenized at low pressure (30 MPa, 3 passes). The higher level of damaged starch might have contributed to increasing the gas production during proofing with consequent higher specific volume of the samples after baking; moreover, lower hardness, as well as higher cohesiveness and resilience were found in the GF breads after the incorporation of the homogenized flours.…”
Section: Physical Treatmentsmentioning
confidence: 99%
“…As part of physical treatments, low-pressure homogenization has recently been applied with interesting results in GF breadmaking. Boulemkahel et al (2022) reported that long/medium grain rice flours showed reduced particle size and an increased content of damaged starch after being homogenized at low pressure (30 MPa, 3 passes). The higher level of damaged starch might have contributed to increasing the gas production during proofing with consequent higher specific volume of the samples after baking; moreover, lower hardness, as well as higher cohesiveness and resilience were found in the GF breads after the incorporation of the homogenized flours.…”
Section: Physical Treatmentsmentioning
confidence: 99%